Comparative analysis of the traffic accidents in the territory of the city of Užice for 2021 and 2022 using open data and the Streamlit application - Gavrilović, Branko M.; Mitrović, Jelena (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: With the development of information technologies, the Internet and social networks, the amount of collected data grows year by year at high speed. Data processing and analysis is becoming a necessity without which quality business decisions cannot be made. With the development of data science, tools for processing unstructured data have also been developed. Open data is publicly available data, the processing of which allows gaining new knowledge. The goal of the work is to present the possibility of using open data for research purposes, and their processing through the Streamlit development environment.Methods: This paper will present the Streamlit framework of the Python programming language and its functionality through the analysis of a web application for data analytics. As a case study, a comparative analysis of the traffic accident data on the territory of the Užice Police Department for 2021 and 2022 will be presented.Results: The Streamlit application will be used for the automatic analysis of open data on the traffic accidents in the territory of the Republic of Serbia in order to process the data and test the hypothesis about whether there has been an increase in traffic safety in the territory of the Užice Police Department.Conclusion: This work shows the possibility of using the Streamlit framework for creating an application for processing open data.
Keywords: Descriptive analytics; open data; Streamlit; Pandas; Python; traffic accidents